Simulation analysis of energy absorption capacity of 3D printed structure design - See, Benjamin Han Xiang (Nanyang Technological University, 2023)
Additive Manufacturing (AM) has made great strides in creating lightweight cellular structures, like lattice structures, which provide benefits like high strength-to-weight ratios and excellent energy absorption abilities. While most research has focused on singular lattice structures, combining different lattices and hierarchical arrangements could lead to improved energy absorption. In this study, the energy absorption capability of the 3D specially designed lattice structure was investigated using finite element analysis. The structures were tested in three different orientations under compression and impact simulations using ANSYS Workbench software. The results demonstrated that different orientations of the structure exhibit varying energy absorption capabilities. Compression in the z-axis had the highest energy absorption at 180 J, while x-axis compression had the highest energy absorption capacity at 168 MJ/m³. Impact in the x-axis displayed the highest energy absorption at 46.6 J, although differences between the orientations were minimal. The absorption capacity was also the highest at 172.2 MJ/m³ in the x-axis impact. The 3D structural design proved to be relatively strong and capable of withstanding significant stress loads. These findings support the potential of these structures for applications in aerospace, marine, and transportation industries. More research is needed to investigate how various lattice structures and hierarchical arrangements can be combined to create even more effective and high-performing designs.